Accelerated ageing test for vigour assessment of pigeon pea Cajanus cajan (L.) Millsp. seeds - Sanches, Mauricio Feis Ganz [UNESP]; dos Santos, Juliana Faria [UNESP]; Martins, Cibele Chalita [UNESP]; de Souza, Francisco Humberto Dübbern; Vieira, Roberval Daiton [UNESP] (My University, 2014)
Pigeon pea [Cajanus cajan (L.) Millsp.] is widely cultivated in tropical areas of the world and it is used as a green manure and forage. The accelerated ageing test is one of the most frequently used tests to evaluate the physiological potential of seeds, however, accurate and adjusted procedures for this test are still missing for pigeon pea seeds. Thus, the aim of the present study was to establish the best combination of conditions to submit pigeon pea seeds to the accelerated ageing test. Five pigeon pea seed lots (cv. Mandarim) were subjected to germination (paper and sand substrate), vigour (first count of germination and emergence speed index) and seedling emergence in the field tests. For the accelerated ageing test procedure, seeds were placed uniformly in a single layer on a fine-mesh tray suspended over 40mL of water (traditional procedure) or saturated salt solution (40% of NaCl), being kept at 42 and 45 °C for 24, 48, 72 and 96 hours. After each period of exposure to the accelerated ageing test, seeds were submitted to the germination test (paper substrate) with seedling evaluation at four, six, eight and ten days after sowing in order to identify the best time for seedlings evaluation. The data were subjected to analysis of variance and treatments were distributed in a completely random design (CRD) with four repetitions. Means were compared with the Tukey test at the 5% level of probability. The results indicated that the traditional accelerated ageing method for pigeon pea seeds should be carried out using the combination of 24 hours and 42 °C with the seedlings evaluation after six days of germination. The accelerated aging test with saturated salt solution should be accomplished using the combinations of 48 hours and 42 °C, with seedlings evaluation after six days of germination and 24 hours and 45 °C with evaluation after four days of germination.
Keywords: Cajanus cajan (L.) Millsp; Physiological potential; Procedure adjustments; Seed quality; Vigour